Mirizzi Syndrome in Gallstone Complication - Ario Perbowo; Dadang Makmun (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Mirizzi syndrome is a rare complication of gallstone which is characterized by the presence of gallstone impaction in cystic duct that leads to inflammatory stricture in the biliary duct and results in obstructive jaundice. In this report, we highlighted the diagnostic approach and management of Mirizzi syndrome in a 58 year-old male complaining of nausea, vomiting, and appearing jaundice. The role of imaging such as abdominal ultrasonography in depicting the characteristics of Mirizzi syndrome was also discussed and compared the findings with the classification of the disease in the literature. In this patient, Mirizzi syndrome was suspected by the appearance acoustic shadow in the gallbladder with dilated cystic duct suggesting the impaction of common bile duct (CBD). We performed endoscopic retrograde cholangiopancreatography (ERCP) as both diagnostic and therapeutic modalities by which we allowed sphingterectomy to evacuate the gallstone. However, due to the risk of further stone evacuation, the procedure was followed by elective cholecystectomy. Keywords: gallstone, Mirizzi syndrome, complication